2018
DOI: 10.1016/j.eurpsy.2018.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics associated with paedophilia and child sex offending – Differentiating sexual preference from offence status

Abstract: Contrary to public perception, child sex offending (CSO) and paedophilia are not the same. Only half of all cases of CSO are motivated by paedophilic preference, and a paedophilic preference does not necessarily lead to CSO. However, studies that investigated clinical factors accompanying and contributing to paedophilia so far mainly relied on paedophiles with a history of CSO. The aim of this study was to distinguish between factors associated with sexual preference (paedophile versus non-paedophile) and offe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 50 publications
(97 reference statements)
3
61
0
2
Order By: Relevance
“…Recruitment was carried out by providing study advertisement/information in diverse internet platforms and some correctional services in Germany. From the total NeMUP sample described elsewhere [Gerwinn et al, ], fMRI data of a total of 117 male subjects matched with respect to age and IQ were analyzed. Accordingly, 77 subjects met ICD‐10 diagnostic criteria for pedophilia.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recruitment was carried out by providing study advertisement/information in diverse internet platforms and some correctional services in Germany. From the total NeMUP sample described elsewhere [Gerwinn et al, ], fMRI data of a total of 117 male subjects matched with respect to age and IQ were analyzed. Accordingly, 77 subjects met ICD‐10 diagnostic criteria for pedophilia.…”
Section: Methodsmentioning
confidence: 99%
“…However, up to now, studies addressing the neurobiological correlates in this regard are scarce and most of them showed inconsistent results [Mohnke et al, ; Tenbergen et al, ]. The only replicated finding is limited to an amygdala volume reduction in offending pedophiles [Poeppl et al, ; Schiffer et al, ; Schiltz et al, ], although other authors using more stringent type‐1 error correction did not corroborate this result [Cantor et al, ; Cantor et al, ; Gerwinn et al, ], suggesting insufficient effect sizes of the aberrant amygdala volume. In addition, there are studies reporting evidence for frontocortical neural dysfunction in pedophiles with a history of CSO (P + CSO) as indicated by regionally decreased brain volume [Mendez and Shapira, ; Schiffer et al, ], impaired neuro‐cognitive functions [Kruger and Schiffer, ; Schiffer and Vonlaufen, ], as well as altered activity in prefrontal areas comprising the orbitofrontal cortex (OFC) [Habermeyer et al, ], dorsolateral prefrontal cortex (DLPFC) [Schiffer et al, ], and the anterior cingulate cortex (ACC) [Schiffer et al, ] during the processing of sexual stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…Sexual fantasies of prepubescent children were also positively associated with sexual offending against children (most frequently CSEM-use). However, as noted by Seto (2010) not all persons admitting sexual interest in children would meet the necessary DSM-5 diagnostic criteria for paedophilic disorder in terms of symptom intensity and persistence and only 20-50% of people who commit sexual offences against children can be classified as paedophilic (Gerwinn et al 2018;Schmidt et al 2013). It is also the case that many men who self-identify as having paedophilic interests do not engage in sexual activity with children or CSEM use (Cohen et al 2018) and evidence higher inhibition (Kärgel et al 2016).…”
Section: Online Deviance Paedophilic Interests and Csemmentioning
confidence: 99%
“…However, even if we get better results, we still face the general problem of interpreting neurobiological 14 The NeMUP researchers found that executive dysfunctions are related to offense status rather than pedophilic preference (68). Furthermore, they revealed that offenders and non-offenders differed in age, intelligence, educational level and experience of childhood sexual abuse, whereas pedophiles and non-pedophiles mainly differed in sexual characteristics (e.g., additional paraphilias) (69). When they compared convicted and non-convicted pedophilic child sexual offenders, they found only two significant differences between the two groups.…”
Section: Neurobiological Findings In Pedophilic Disorder and Aspdmentioning
confidence: 99%
“…Furthermore, they revealed that offenders and non-offenders differed in age, intelligence, educational level and experience of childhood sexual abuse, whereas pedophiles and non-pedophiles mainly differed in sexual characteristics ( e.g. , additional paraphilias) ( 69 ). When they compared convicted and non-convicted pedophilic child sexual offenders, they found only two significant differences between the two groups.…”
mentioning
confidence: 99%